Differentiated learning with information technology for teachers at SMA Negeri 5 Padangsidimpuan - Jaya, Ivan; Hardi, Sri Melvani; Elveny, Marischa (Journal of Saintech Transfer, 2024)
Differentiated learning aims to improve classroom learning by accommodating students' diverse personalities and backgrounds, enabling effective and efficient participation. This community service provides training for teachers at SMA Negeri 5 Padangsidimpuan on differentiated learning methods using information technology through a blended learning approach. The training included pre- and post-tests to evaluate teachers' knowledge and skills. Results showed a significant improvement in teachers' ability to use interactive applications such as Padlet, Nearpod, Classcraft, and Kahoot, with post-test scores indicating an average increase of 20% compared to pre-test scores. Statistical analysis using the T-test confirmed the enhancement, with p-values below 0.05 for differentiated learning concepts and application usage. Teachers reported Kahoot as the most preferred application, followed by Padlet, Classcraft, and Nearpod. The study concludes that designing and implementing diverse instructional strategies using interactive media tailored to students' needs fosters meaningful learning experiences and improves teaching outcomes. Future efforts will include sustained support for teachers and the development of technology-focused learning modules.